2022
DOI: 10.1038/s41522-022-00346-4
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm antimicrobial susceptibility through an experimental evolutionary lens

Abstract: Experimental evolution experiments in which bacterial populations are repeatedly exposed to an antimicrobial treatment, and examination of the genotype and phenotype of the resulting evolved bacteria, can help shed light on mechanisms behind reduced susceptibility. In this review we present an overview of why it is important to include biofilms in experimental evolution, which approaches are available to study experimental evolution in biofilms and what experimental evolution has taught us about tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 153 publications
0
22
0
Order By: Relevance
“…These biofilm features allow bacteria to access more fitness peaks in rugged adaptive landscapes. This can result in evolutionary outcomes that may not be observed in planktonic populations that routinely experience strong selective sweeps [40][41][42] . Previously we showed that under antibiotic selection, evolution in biofilms results in a higher diversity of plasmid persistence phenotypes as compared to planktonic populations 43 .…”
Section: Introductionmentioning
confidence: 99%
“…These biofilm features allow bacteria to access more fitness peaks in rugged adaptive landscapes. This can result in evolutionary outcomes that may not be observed in planktonic populations that routinely experience strong selective sweeps [40][41][42] . Previously we showed that under antibiotic selection, evolution in biofilms results in a higher diversity of plasmid persistence phenotypes as compared to planktonic populations 43 .…”
Section: Introductionmentioning
confidence: 99%
“…The pellet was resuspended in a new LB medium and diluted to prepare three samples with 0.1, 0.5, and 1.0 OD 600 . Antibiotic-resistant P. aeruginosa was obtained by repeatedly exposing the bacteria to low concentrations of each antibiotic, GEM, CIP, and AMP, 32 and their resistance was confirmed by the disk diffusion test (Fig. S3 †).…”
Section: Fabrication Of the Ast Arraymentioning
confidence: 94%
“…This in vitro experimental evolution of bacteria to antibiotics has been commonly used to identify the mechanisms of antibiotic resistance. 32,33…”
Section: Fabrication Of the Ast Arraymentioning
confidence: 99%
“…These biofilm features allow bacteria to access more fitness peaks in rugged adaptive landscapes. This can result in evolutionary outcomes that may not be observed in planktonic populations that routinely experience strong selective sweeps 4042 . Previously we showed that under antibiotic selection, evolution in biofilms results in a higher diversity of plasmid persistence phenotypes as compared to planktonic populations 43 .…”
Section: Introductionmentioning
confidence: 99%
“…These biofilm features allow bacteria to access more fitness peaks in rugged adaptive landscapes. This can result in evolutionary outcomes that may not be observed in planktonic populations that routinely experience strong selective sweeps [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%